HYBRID QUICKSORT: AN EMPIRICAL STUDY - Sujarwo, Surya (CommIT (Communication and Information Technology) Journal, 2013)
This article describes an empirical study of hybrid approach of quicksort algorithms. The hybrid approach uses various variations of quicksort partition algorithms in combination with cutoff to shellsort using several cutoff elements. The paper compares the running time performance of the existing quicksort partition algorithms with the proposed hybrid approachusing uniqueand duplicate elements. As a result, it is found that several the hybrid approaches performs faster than the existing algorithms for uniqueand duplicate elements.